The Social Reaction for The Effort of Crime Prevention (In The Short Analizing) - Faisol Azhari (Jurnal Hukum, 2014)
Really, talking about the problem of the social reaction  for the crime and offenders in the development of criminology science are so important. Therefore in analizing for that case and  how to solve about crime  the criminology science isn’t limmited about the background of crime only or law.       The crime prevention is also explained by Criminology. Therefore Criminology is also include the study of the social reaction against crime. Edwin H Sutherland and Cressey said that the crime prevention or the social reaction against crime include within criminology. And really, accordance with the development of criminology science it needs the other sciences to support it in analizing  for crime and crime causation such as the anthropology science phsichology science sociology criminal science etc. There are several approaches analizing about the crime and the effort of crime prevention.Keywords: The crime prevention, The social reaction against crime